Analysis of the Role of Psychological Factors in Learning Outcomes in Physical Education (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This study examined the impact of four psychological factors—motivation, self-confidence, autonomy, and personal and social responsibility—on learning outcomes in physical education among grade X students in Narmada District, Lombok Barat. While prior studies have explored these factors individually, limited research addresses their combined influence. This ex-post facto study employed questionnaires to measure psychological traits and academic records to assess student outcomes. Regression analysis revealed significant positive correlations between each psychological factor and physical education performance. Motivation and autonomy had the strongest effects, accounting for 52% and 55% of the variance, respectively. Self-confidence explained 46% and personal and social responsibility 50%. Notably, self-confidence and responsibility also demonstrated moderate correlations with academic performance (r = 0.68 and r = 0.71, respectively). These findings highlight the integral role of psychological development in shaping physical education outcomes. Motivation boosts engagement, while autonomy—enabled through choice and self-direction—enhances both participation and performance. Though self-confidence and responsibility had slightly lesser effects, they remain vital contributors to success. The study underscores the importance of creating a learning environment that fosters psychological strengths alongside physical skills. Integrating these factors into physical education programs can enhance student engagement, accountability, and academic achievement. Educators are encouraged to adopt autonomy-supportive and responsibility-building strategies to support holistic development. The study concludes by advocating for continued research into the long-term effects of these psychological traits and their interactions. Emphasizing both mental and physical growth is essential for promoting sustainable student success in physical education contexts.